Understanding hysteresis in discrete multi-articular action performed by skilled and novice table tennis players - Rizal, W.; Chow, J. Y.; Rein, R. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
From a dynamical systems perspective, self-organization is a key tenet in understanding human movement and may be examined via phenomenon at the phase transition point. Amongst the phenomenon is hysteresis. Hysteresis refers to the influence of previous experience on the next movement pattern. The aim of this study is to examine hysteresis through the investigation of movement patterns in a table tennis task. Skilled (n=10) and novice participants (n=10) were required to return balls delivered in a scaling manner by a feeding machine to nine locations back to a target. 3D kinematic data of the upper body was captured and digitised and results were obtained using the cluster analysis approach. A six point nominal scale was used to record performance. Cluster analysis resulted in two movement patterns for skilled and seven for novices. Hysteresis region for novices were notably larger, spanning over eight locations as compared to the skilled participants` two locations. This highlights the inability of novices in utilising the most suitable task solution at any particular solution and further supports the trait of heightened exploration in less skilled participants. The numerous variations of movement patterns adopted by novices indicates their exploration for the most suitable task solution and infers the presence of meta-stability and degeneracy expected from a discrete multi-articular task. Results for hysteresis indicate that this phenomenon may be a function of skill levels therefore, it may be used as a tool to dichotomise skill levels. In that regard, coaches should adopt training sessions that encourages players to practice a variety of spatial locations that may improve their decision-making skills.